Localization of the Dantrolene-binding Sequence near the FK506-binding Protein-binding Site in the Three-dimensional Structure of the Ryanodine Receptor - Wang, Ruiwu (American Society for Biochemistry and Molecular Biology, 2011)
Dantrolene is believed to stabilize interdomain interactions between the NH(2)-terminal and central regions of ryanodine receptors by binding to the NH(2)-terminal residues 590–609 in skeletal ryanodine receptor (RyR1) and residues 601–620 in cardiac ryanodine receptor (RyR2). To gain further insight into the structural basis of dantrolene action, we have attempted to localize the dantrolene-binding sequence in RyR1/RyR2 by using GFP as a structural marker and three-dimensional cryo-EM. We inserted GFP into RyR2 after residues Arg-626 and Tyr-846 to generate GFP-RyR2 fusion proteins, RyR2(Arg-626-GFP) and RyR2(Tyr-846-GFP). Insertion of GFP after residue Arg-626 abolished the binding of a bulky GST- or cyan fluorescent protein-tagged FKBP12.6 but not the binding of a smaller, nontagged FKBP12.6, suggesting that residue Arg-626 and the dantrolene-binding sequence are located near the FKBP12.6-binding site. Using cryo-EM, we have mapped the three-dimensional location of Tyr-846-GFP to domain 9, which is also adjacent to the FKBP12.6-binding site. To further map the three-dimensional location of the dantrolene-binding sequence, we generated 10 FRET pairs based on four known three-dimensional locations (FKBP12.6, Ser-437-GFP, Tyr-846-GFP, and Ser-2367-GFP). Based on the FRET efficiencies of these FRET pairs and the corresponding distance relationships, we mapped the three-dimensional location of Arg-626-GFP or -cyan fluorescent protein, hence the dantrolene-binding sequence, to domain 9 near the FKBP12.6-binding site but distant to the central region around residue Ser-2367. An allosteric mechanism by which dantrolene stabilizes interdomain interactions between the NH(2)-terminal and central regions is proposed.